Autobiography as Counter-Narrative: An Empirical Study of How Race Enters and Structures the Stories of Our Lives - Wendy B. Yanow (Adult Education Research Conference, 2007)
Using Critical Race Theory (CRT) as a lens through which to examine learning autobiography, and counter-storytelling as a method of CRT, this study offers a view of the world from the perspective of adult students’ racialized experiences.